Multiply. Express your answer as a polynomial in standard form. (1 point)

(2x+5)(2x−5)=
(
2
𝑥
+
5
)
(
2
𝑥

5
)
=

1 answer

To multiply the two binomials \( (2x + 5)(2x - 5) \), we can use the difference of squares formula, which states that \( (a+b)(a-b) = a^2 - b^2 \).

Here, let \( a = 2x \) and \( b = 5 \). Thus, we have:

\[ (2x + 5)(2x - 5) = (2x)^2 - (5)^2 \]

Now, calculate each square:

\[ (2x)^2 = 4x^2 \quad \text{and} \quad (5)^2 = 25 \]

Substituting back into the difference of squares formula gives:

\[ 4x^2 - 25 \]

Thus, the product expressed as a polynomial in standard form is:

\[ \boxed{4x^2 - 25} \]

Similar Questions
    1. answers icon 1 answer
  1. Given: f(x)=2x^2+x-3 and g(x)=x-1Express: f(x)⋅g(x)-[f(x)+g(x)] as a polynomial in standard form
    1. answers icon 1 answer
  2. PLS HELP ME!!I really need the answers to these few questions I need toturn them in ASAP. Simplify each polynomial. Write each
    1. answers icon 2 answers
    1. answers icon 7 answers
more similar questions